2019 IEEE International Conference on Healthcare Informatics (ICHI) 2019
DOI: 10.1109/ichi.2019.8904863
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Twitter to Identify Topics Related to Eating Disorder Symptoms

Abstract: Eating disorders (EDs) are serious mental illnesses associated with physical and psychiatric problems, and premature death. Examining social media communication about ED symptoms may provide insight into how to prevent and treat these disorders. This study is to explore topics on Twitter related to EDs. We applied the Correlation Explanation (CorEx) topic model on 18,288 ED-related tweets and identified 20 topics, which were further grouped into 8 categories. The top two topic categories are body image and ED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 13 publications
2
22
0
Order By: Relevance
“…Compared with our previous study [ 17 ], several new topics were identified, including Questions or Concerns , Reflection or Planning , Comorbidity , Ambivalence , Insults , and Diagnostic criteria. Textbox 3 shows these topic themes and example tweets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with our previous study [ 17 ], several new topics were identified, including Questions or Concerns , Reflection or Planning , Comorbidity , Ambivalence , Insults , and Diagnostic criteria. Textbox 3 shows these topic themes and example tweets.…”
Section: Resultsmentioning
confidence: 99%
“…The CorEx model identifies the topics that are maximally informative about a collection of documents [ 25 ]. The BTM and the CorEx model were tested in our preliminary study [ 17 ], and the CorEx model was adopted because it produced more meaningful topics using our collected tweets.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such work demonstrated the capability of this novel technique to extract topics able to separate multiple facets within each analyzed discussion. Along this line, authors in [50] applied CorEx to tweets concerning eating disorders. They extracted novel topics and provided insights into factors that may foster the perpetuation of such behaviors, thus contributing to better understand -and possibly deal -with this serious issue.…”
Section: Invite Link Network Enrichment: Characterizing Online Crmentioning
confidence: 99%